Pelaksanaan Model Problem Based Learning (PBL) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa di SMA Negeri 7 Padang - Karlina, Riski; Wirdati, Wirdati (AS-SABIQUN, 2023)
In the 21st century, there are many challenges faced by teachers and students in the world of education, especially in the learning aspect. Where the teacher serves as a facilitator for students in order to train students' critical thinking skills. While students are required to be able to hone their critical thinking skills so that they are able to deal with problems that occur in their lives, both in the present and in the future. Efforts that can be made by teachers in honing students' critical thinking skills are one of them by applying the PBL model. PBL is one model that teachers can use to help improve students' critical thinking skills. Padang 7 Public High School is a driving school that has implemented the PBL model, especially in PAI subjects in the material Faith in Qada and Qadar. This study aims to find out how the implementation of the PBL model on the material Faith in Qada and Qadar at SMA Negeri 7 Padang. The method used in this research is a qualitative method with a case study type. The data sources for this study were Islamic Religious Education teachers, curriculum representatives and 5 students of class XII IPA 6 SMA Negeri 7 Padang. The instruments used were interview guidelines and observation guidelines. Data collection techniques used are interviews, observation and documentation. While the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. And for the data validity technique used is source and technique triangulation. The results of this study indicate that the implementation of the Problem Based Learning (PBL) model in the material Faith in Qada and Qadar can improve students' critical thinking skills as evidenced by the implementation of all indicators of critical thinking in the learning process and have fulfilled the PBL syntax, namely problem orientation towards students, organizing students, guiding individual and group investigations, developing and presenting work, analyzing and evaluating problem-solving processes.